Galactic binaries can explain the Fermi Galactic centre excess and 511 keV emission. Issue 3 (8th August 2018) - Bartels, R; Calore, F; Storm, E; Weniger, C
ABSTRACT: The Fermi –LAT Galactic Centre excess and the 511 keV positron-annihilation signal from the inner Galaxy bear a striking morphological similarity. We propose that both can be explained through a scenario in which millisecond pulsars produce the Galactic Centre excess and their progenitors, low-mass X-ray binaries, the 511 keV signal. As a proof of principle, we study a specific population synthesis scenario from the literature involving so-called ultracompact X-ray binaries. Moreover, for the first time, we quantitatively show that neutron star, rather than black hole, low-mass X-ray binaries can be responsible for the majority of the positrons. In this particular scenario, binary millisecond pulsars can be both the source of the Fermi –LAT γ-ray excess and the bulge positrons. Future avenues to test this scenario are discussed.